EFEKTIVITAS PENERAPAN SISTEM INFORMASI PEMERINTAH DAERAH (SIPD) PADA DINAS KETAHANAN PANGAN KABUPATEN SINJAI - Musyarrifa, Izzatul; Razak, Andi Rosdianti; Yusuf, Muh (Universitas Muhammadiyah Makassar, 2024)
This research uses qualitative descriptive qualitative methods. Data collection techniques include observation, interviews and documentation. The results of the research are the application of the Regional Government Information System (SIPD) to support the implementation of financial reports for the Sinjai Regency Food Security Service which began to be implemented in 2019, which was an initiation from the Ministry of Administrative and Bureaucratic Reform. The Regional Government Information System (SIPD) is planning for the Regional Apparatus Organization (OPD) for the next year and from that planning it can contain financial planning that can be used by the financial treasurer which will later become a budget work plan document and a list of budget implementers, then this document will be used by the treasurer in implementation. financial reporting of the Sinjai Regency Food Security Service. With the implementation of the Regional Government Information System (SIPD), it can be reported, informed effectively and efficiently in managing regional financial reports in a transparent and accountable manner and can speed up or make government work more effective.